2011
DOI: 10.1080/07055900.2011.594024
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Surface Features of the 1999–2005 Canadian Prairie Drought in Relation to Previous Severe Twentieth Century Events

Abstract: The Canadian Prairie drought of 1999-2005 negatively affected several activities including agriculture, stream flow, hydro-electric production and forest fires. However, surface drought conditions and associated impacts were neither spatially nor temporally uniform. Following an assessment of several gridded temperature and precipitation datasets, this study incorporates the Standardized Precipitation Index (SPI) and the Palmer Drought Severity Index (PDSI) to characterize the surface features of the 1999-2005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…The approach adopted in this study could be extended to groundwater level records as a further line of research. Similar variability in drought terminations was reported by Bonsal et al (2011), and was attributed by Kam et al (2013) to differences in rainfall intensity determined by the synoptic conditions (e.g. tropical cyclones).…”
Section: Drought Termination Rate For 2009-2012 In a Historical Contextsupporting
confidence: 49%
See 2 more Smart Citations
“…The approach adopted in this study could be extended to groundwater level records as a further line of research. Similar variability in drought terminations was reported by Bonsal et al (2011), and was attributed by Kam et al (2013) to differences in rainfall intensity determined by the synoptic conditions (e.g. tropical cyclones).…”
Section: Drought Termination Rate For 2009-2012 In a Historical Contextsupporting
confidence: 49%
“…Drought termination is characterized by its duration (e.g. Bonsal et al, 2011), rate of change (e.g. Correia et al, 1987;Nkemdirim and Weber, 1999), and seasonality (e.g.…”
Section: Defining Drought Terminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst most concepts of drought termination do not account for this, Mo (2011) introduced a 'transition time' at the end of a drought and Bonsal et al (2011) suggested the partitioning of drought into six distinct parts, one of which is a 'recovery' phase. The approach described below builds upon these concepts.…”
Section: A Novel Approachmentioning
confidence: 99%
“…Bonsal et al (2011b) utilize drought indices and related parameters to document the evolution of this drought and to compare its features with others. The study incorporates the Standardized Precipitation Index and the Palmer Drought Severity Index to characterize the surface features of the 1999-2005 Prairie drought in terms of its region of origin, propagation, persistence and termination.…”
Section: Following Articlesmentioning
confidence: 99%